Silver colloidal nanoparticle stability: influence on Candida biofilms formed on denture acrylic - Monteiro, D. R. (2014)
Our aim in this study was to evaluate how the chemical stability of silver nanoparticles (SNs) influences their efficacy against Candida albicans and C. glabrata biofilms. Several parameters of SN stability were tested, namely, temperature (50ºC, 70ºC, and 100ºC), pH (5.0 and 9.0), and time of contact (5 h and 24 h) with biofilms. The control was defined as SNs without temperature treatment, pH 7, and 24 h of contact. These colloidal suspensions at 54 mg/L were used to treat mature Candida biofilms (48 h) formed on acrylic. Their efficacy was determined by total biomass and colony-forming unit quantification. Data were analyzed using analysis of variance and the Bonferroni post hoc test (=0.05). The temperature and pH variations of SNs did not affect their efficacy against the viable cells of Candida biofilms (P > 0.05). Moreover, the treatment periods were not decisive in terms of the susceptibility of Candida biofilms to SNs. These findings provide an important advantage of SNs that may be useful in the treatment of Candida-associated denture stomatitis.